An oyster species-specific miRNA scaffold42648_5080 modulates haemocyte migration by targeting integrin pathway. (October 2016) - Chen, Hao; Wang, Hao; Jiang, Shuai; Xu, Jiachao; Wang, Lingling; Qiu, Limei; Song, Linsheng
Abstract: miRNAs are important gene regulators at post-transcriptional level and can modulate diverse biological processes, including immune response. Dozens of species-specific miRNAs have been identified in oyster Crassostrea gigas while their functions remain largely unknown. In the present study, an oyster species-specific miRNA scaffold42648_5080 was found responsive to LPS stimulation and might target a total of 31 oyster genes possibly involved in cell communication, cellular localization and cellular response to stimulus. Besides, in gain-of-function assay of scaffold42648_5080 in vivo, the phagocytosis (30.90% in miRNA group verse 23.20% in miRNA control group), apoptosis (3.10% in miRNA group verse 5.30% in miRNA control group) and migration rate (13.88% in miRNA group verse 21.03% in miRNA control group) of oyster haemocytes were found significantly altered after the injection of scaffold42648_5080 mimics. Among the target genes, integrin-linked kinase (CgILK) was considered crucial in cell migration and its interaction with scaffold42648_5080 was then verified both in vitro and in vivo . Consequently, a significant decrease of relative luciferase ratio was observed in CgILK 3′-UTR luciferase reporter assay after transfection of scaffold42648_5080 mimics (0.70-fold of that in blank group, p  < 0.01). Meanwhile, when scaffold42648_5080 was overexpressed in vivo (5.41-fold of miRNA control group, p  < 0.01), the expression of CgILK declined significantly to 0.25-fold of miRNA control group ( p  < 0.01). Comparatively, a significant decrease of the haemocyte migration rate (19.76% verse 34.82% in siEGFP control group, p  < 0.01) was observed after knock-down of CgILK in vivo . The present study, as far as we know, for the first time revealed the immunomodulation role of an oyster species-specific miRNA, which might provide new insights into miRNA-mediated adaptation mechanism of oysters. Highlights: Scaffold42648_5080 was identified as an oyster species-specific miRNA. Scaffold42648_5080 could be fast induced after LPS challenge in primary haemocytes. Cellular immune responses of oyster haemocytes were modulated by scaffold42648_5080. Migration of oyster haemocytes could be modulated by scaffold42648_5080 via targeting CgILK.